1981
DOI: 10.1038/clpt.1981.200
|View full text |Cite
|
Sign up to set email alerts
|

Ranitidine kinetics and dynamics: I. Oral dose studies

Abstract: Ranitidine, an H2-receptor antagonist, has been shown to reduce pentagastrin-stimulated gastric secretion. We examined the relationship between inhibition of gastric secretion and ranitidine serum concentration. Twelve normal male subjects received 20, 40, or 80 mg of ranitidine orally 90 min before starting a 3-hr continuous infusion of pentagastrin, 2 micrograms/kg/hr. Ranitidine, 20, 40, and 80 mg, reduced hydrogen ion output by 29%, 50%, and 70% and secretion volume by 21%, 37%, and 47%. Pepsin activity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

1985
1985
1993
1993

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 1 publication
3
14
0
Order By: Relevance
“…The t,~ in our subjects following intravenous dosing was 7.07 + 0.96 h which is a value that approximates that of 7.3 h observed by McFadyen et al [12] in near end-stage chronic renal failure patients and is similar to the value of 9.03 _+ 1.45 (SD) h demonstrated by Zech et al [25] in a like patient population. Like a number of other studies [1,4,8,14] we observed a higher ranitidine elimination t,~ following oral dosing (10.02 h). This phenomenon is not completely understood but may relate to prolonged absorption from the oral dosage form.…”
Section: Discussionsupporting
confidence: 63%
“…The t,~ in our subjects following intravenous dosing was 7.07 + 0.96 h which is a value that approximates that of 7.3 h observed by McFadyen et al [12] in near end-stage chronic renal failure patients and is similar to the value of 9.03 _+ 1.45 (SD) h demonstrated by Zech et al [25] in a like patient population. Like a number of other studies [1,4,8,14] we observed a higher ranitidine elimination t,~ following oral dosing (10.02 h). This phenomenon is not completely understood but may relate to prolonged absorption from the oral dosage form.…”
Section: Discussionsupporting
confidence: 63%
“…respec tively. Mignon et al [22] have demonstrated 50 and 80% reductions in acid output with ranitidine concentrations of 73 and 180 jj.g/1, respectively, which is consistent with other reports [23][24][25], Based on the mean bioavailability, elimination half-life, and volume of distribution in our patients, an approximate serum ranitidine concentration of 350 ¡.tg/i would result from a daily 150 mg oral dose if hemodialysis were not superimposed. For multiple intra venous dosing, 50 mg every 12-24 h should maintain serum concentrations consistently above 100 ug/1.…”
Section: Discussionsupporting
confidence: 79%
“…The question of whether ranitidine maintenance dose should be reduced in this patient group is not easy to answer since overall only 58% of gastric aspirate samples had pH values which were compatible with effective suppression of acid secretion (i.e., pH > 4). This response rate occurred despite trough plasma ranitidine concentrations which were similar to (median = 0.11 mg [-1, range = 0.05-1.44 mg [71) those required to cause a 50% suppression of gastric acid secretion (range of means = 0.073-0.2 mg [-1) in healthy volunteers (Lebert et al, 1981b;Mignon et al, 1982;Holloway et al, 1984). Moreover, four of our patients failed to achieve significant elevation of gastric pH at any of the times at which measurements were made.…”
Section: Discussionmentioning
confidence: 99%